2023
DOI: 10.1051/e3sconf/202342602024
|View full text |Cite
|
Sign up to set email alerts
|

Green Accounting and Disclosure of Sustainability Report on Firm Values in Indonesia

Tri Ayu Astari,
Sebastianus Laurens,
Aries Wicaksono
et al.

Abstract: The industry must deal with environmental issues by implementing green accounting and disclosure of sustainability reports. This study aimed to determine the effect of implementing green accounting and disclosure of sustainability reports on firm value. The research was conducted in Indonesia Manufacturing companies with an observation period of 2019-2021. The data analysis technique used is Multiple Linear Regression Analysis. The study results show that applying green accounting has a positive effect on firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…Additional studies have shown conflicting findings, suggesting that green accounting may have a detrimental impact on business value. These conclusions are supported by the research conducted by (Astari et al, 2023;Lindawati et al, 2023;Nuswandari et al, 2019;Sukmadilaga et al, 2023).…”
Section: Introductionsupporting
confidence: 64%
“…Additional studies have shown conflicting findings, suggesting that green accounting may have a detrimental impact on business value. These conclusions are supported by the research conducted by (Astari et al, 2023;Lindawati et al, 2023;Nuswandari et al, 2019;Sukmadilaga et al, 2023).…”
Section: Introductionsupporting
confidence: 64%